Fine altitude resolution radar observations of upper-tropospheric and lower-stratospheric winds and waves - Sato, Toru (1982)
Preliminary results of wind velocity measurements made using the Arecíbo 430 MHz radar are presented. These measurements were made in the altitude range between 10 and 30 km, with a time resolution of 1-2 min, and an improved altitude resolution of 150 m. A few interesting phenomena such as a quasistationary wavy structure and short period sinusoidal oscillations are discussed.